Analisis Pedagogi Pembelajaran Abad 21 dan Kesesuaian Konsep Ikatan Kimia Pada Video Channel Youtube - Muhammad Naufal Pasha; Sadiana, I Made; Fatah, Abdul Hadjranul (FKIP Universitas Palangka Raya, 2024)
This study aims to: (1) describe the alignment of Chemical Bonding concepts in YouTube channel videos with the 2013 curriculum, (2) describe the alignment of chemical bonding concepts in YouTube channel educational videos with 21st-century learning aspects (4C), (3) describe the suitability of pedagogy in chemical bonding educational videos on YouTube channels, and (4) explain how the reviewed YouTube channel videos can still support learning. The research method used is a descriptive approach. The object of this study is the concept of chemical bonding in educational videos from YouTube channels. Three educational videos were analyzed and coded as Video A, Video B, and Video C, and were conducted offline in a classroom setting. The instruments used include a concept label identification table, a 2013 curriculum concept label identification table, a 4C skills indicator identification table, and a pedagogy identification table. The identification results were validated by lecturers from the Chemistry Education Study Program at the University of Palangka Raya. The results showed that the concept labels from the three analyzed educational videos amounted to 32 concept labels. The concept labels that align with the 2013 curriculum syllabus are 11 concept labels across Videos A, B, and C. Overall, the 21st-century skills most commonly developed are Communication skills in Video A, Collaboration skills in Video B, and Critical thinking and problem-solving skills in Video C. The pedagogy demonstrated by teachers in YouTube channel educational videos most frequently included indicators of effective, empathetic, and courteous communication with students in Video A, curriculum development related to the subject taught in Video B, and facilitating the development of students' potential to actualize their various abilities in Video C.